The Importance of Inter-Species Variation in Traumatic Brain Injury-Induced Alterations of Microglial-Axonal Interactions - Gorse, Karen M.; Lafrenaye, Audrey D. (Frontiers in Neurology, 2018)
Interactions between microglia and neuronal components are important for normal CNS function. They are also associated with neuroinflammation and many pathological processes and several studies have explored these interactions in terms of phagocytic engulfment. Much progress has also been made in understanding the consequences of chronic neuroinflammatory changes following trauma. However, little is known about acute alterations to these physical non-phagocytic microglial-neuronal interactions following traumatic brain injury (TBI), and particularly to what degree these post-injury interactions may be influenced by the animal species utilized in pre-clinical models of TBI. To investigate these problems, we evaluated the physical interactions between microglia and injured axons acutely (6hr and 1d) following central fluid percussion injury (cFPI) in both rats and micro pigs. The physical interactions between Iba-1+ microglia and either normal MBP+ myelinated fibers or APP+ injured axonal swellings in the thalamus were assessed following injury or sham via quantitative image analysis of 3D confocal micrographs. The results indicated that the physical interactions between microglia and injured axonal swellings decreased by nearly half in rats 6hrs following cFPI but was consistent with sham control at 1d post-cFPI. This reduction was also observed in non-injured intact fibers at both timepoints following TBI in the rat. Microglial process interactions with injured axons in the micro pig, however, increased nearly two fold compared to interactions with intact axonal segments 1d post-cFPI. This study shows that the species utilized for in vivo pre-clinical studies influences the manner in which microglial-axonal interactions change following TBI. These species differences can be leveraged to further our understanding of the mechanisms involved in microglial process convergence and how these neuro-immune interactions alter the progression of axonal injury following TBI.